2017
DOI: 10.12691/jpar-2-2-7
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Health Habits of a Canadian University Community

Abstract: In 2014, World Health Organization reported that more than 1.9 billion people were obese (World Health Organization, 2014). This epidemic is thought to cost $2 trillion globally every year (Dobbs et al., 2014). With the increase of the prevalence of obesity, there is a continuous search for effective obesity-prevention and health promotion strategies. In a Canadian university, Perusse-Lachance and colleagues (2010) showed that 22.9% of students and 37.3% of staff members were either overweight or obese. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
13
1
3
Order By: Relevance
“…The prevalence of overweight and obesity was also lower in both faculties than in the abovementioned study [3]. This can be explained by the education level of the participants in this study, which positively influences the nutritional status [15], although in this study the results were lower compared to a Canadian college students' BMI values [16].…”
Section: Discussioncontrasting
confidence: 58%
“…The prevalence of overweight and obesity was also lower in both faculties than in the abovementioned study [3]. This can be explained by the education level of the participants in this study, which positively influences the nutritional status [15], although in this study the results were lower compared to a Canadian college students' BMI values [16].…”
Section: Discussioncontrasting
confidence: 58%
“…In Canada, research on university students in a prepandemic condition has drawn attention to the reality that they are a vulnerable group for inadequate diet and physical activity. In a recent study at a university in the province of Quebec, 81.2% of students (n = 1989) surveyed did not consume the recommended daily servings of fruits and vegetables whilst 55.2% of students were not meeting the Canadian 24-Hour Movement Guidelines for Adults of 150 min of moderate to vigorous physical activity per week (Busque et al 2017). In an earlier study from another Quebec university, similar results were reported (Perusse-Lachance et al 2010).…”
Section: Introductionmentioning
confidence: 66%
“…In Canada, research on university students in a pre-pandemic condition has drawn attention to the reality that they are a vulnerable group for inadequate diet and physical activity. In a recent study at a university in the province of Quebec, 81.2% of students (n=1989) surveyed did not consume the recommended daily servings of fruits and vegetables whilst 55.2% of students were not meeting the Canadian 24-Hour Movement Guidelines for Adults of 150 minutes of moderate to vigorous physical activity per week (Busque et al, 2017). In an earlier study from another Quebec university, similar results were reported (Perusse-Lachance et al, 2010).…”
Section: Introductionmentioning
confidence: 99%